การขจัดพอลิไซคลิกแอโรแมติกไฮโดรคาร์บอนในน้ำมันไพโรไลซิสจากยางรถยนต์เหลือทิ้ง - สุรีกาญจน์ กิ่งพุทธพงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
Waste tire pyrolysis oil (WTPO) contains the huge volume of polycyclic aromatic hydrocarbon (PAHs) ca. 10 wt% based on WTPO content. Naphthalene, a family of PAHs most commonly found in the WTPO, are claimed as toxic components for organism and environment. This limits the use of untreated WTPO in the combustion engines. In this research, the catalytic hydrogenation was applied for removing naphthalene used as the model compounds of PAHs. Nickel supported on gamma alumina (Ni/γ-Al2O3) with and without the addition of molybdenum (Mo), tungstate (W) or platinum (Pt)-promoter was selected as the catalyst for this process. For the effect of hydrogenation parameters; initial H2 pressure (10-40 bar) temperature (250-400 °C) and reaction times (2-8 h) on the catalytic activity were investigated. Before hydrogenation process, the catalysts were in-situ reduced under 30 bar initial H2 pressure at 400 oC for 2 h. Without the addition of promoter, 1-30 wt% Ni–active metal was deposited onto the γ-Al2O3 prepared via hydrothermal process. The maximum naphthalene conversion detected by gas chromatography-flame ionization detector (GC-FID) was achieved to 29.5% when 20 wt% Ni loading was applied under 30 bar initial H2 pressure at 350 ºC for 4 h. In the case of promoter addition, the naphthalene conversion obtained from NiMo, NiW and NiPt catalyst increased the naphthalene conversion to 44.7%, 46.4% and 55.8%, respectively when the Mo-, W- and Pt-promoter were loaded onto the catalyst with atomic ratio of 0.27, 0.05 and 0.37, respectively. However, Ni and NiPt catalyst were less tolerant to organosulfurous compounds, which could be found in the WTPO. Thus, the NiMo and NiW catalysts containing the promoter atomic ratio at 0.27 and 0.05 were selected for catalyzing the hydrogenation of PAHs in the real WTPO. The experimental results showed that the hydrogenation of WTPO using NiMo and NiW catalysts could decrease the PAHs in WTPO from 59.3% to 18.0% and 36.6%, respectively.